2016
DOI: 10.1292/jvms.15-0583
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the degree of insulin resistance during late gestation and postpartum performance in dairy cows and factors that affect growth and metabolic status of their calves

Abstract: This study aimed to investigate the effects of insulin resistance (IR) during the close-up dry period on the metabolic status and performance of dairy cows as well as to determine the effects on body weight (BW) and metabolic status of their calves. An insulin tolerance test (ITT) was conducted by administering 0.05 IU/kg BW of insulin to 34 multiparous Holstein cows at 3 weeks prepartum. Blood samples were collected at 0, 30, 45 and 60 min after insulin injection, and cows were divided into two groups based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…BCS, serum glucose, NEFA, and T‐Cho concentrations, and serum AST activities were within the standard values for the dry period reported by Kida (). In addition, the changes in plasma concentrations of insulin and leptin, and the serum concentrations of BHB (Zhang, Su, Wang, Cao, & Li, ) and Alb (Kawashima et al, ) during late gestation were within approximately the same ranges as reported previously. Therefore, the herd examined in the present study appeared to have normal levels of the selected metabolites.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…BCS, serum glucose, NEFA, and T‐Cho concentrations, and serum AST activities were within the standard values for the dry period reported by Kida (). In addition, the changes in plasma concentrations of insulin and leptin, and the serum concentrations of BHB (Zhang, Su, Wang, Cao, & Li, ) and Alb (Kawashima et al, ) during late gestation were within approximately the same ranges as reported previously. Therefore, the herd examined in the present study appeared to have normal levels of the selected metabolites.…”
Section: Resultssupporting
confidence: 81%
“…However, little information is currently available regarding the relationships between IR in dairy cows during late gestation, the metabolic status of dams, and their calves. Moreover, although we showed in a previous study that the IR of dairy cows in late gestation is associated with lower calf body weight (BW) immediately after birth (Kawashima et al, ), there is at present no standardized procedure for IR evaluation in cattle, and consequently different studies have tended to adopt different methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketosis, present at either a subclinical or clinical level, is a common metabolic condition in modern highproducing dairy cows (Vanholder et al, 2015). Highyielding dairy cows suffer from negative energy balance (NEB) and decreased insulin sensitivity during early lactation because of energy expenditure resulting from milk production and limited feed intake (Yuan et al, 2012;Kawashima et al, 2016). Negative energy balance initiates fat mobilization and a subsequent increase in the blood concentrations of fatty acids (Gross et al, 2013); high concentrations of fatty acids can impair the insulin signaling pathway, thereby decreasing the insulin sensitivity (Barazzoni et al, 2012;Gao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, high yielding dairy cattle are prone to insulinoresistance because of their high energy requirements for milk production inducing a negative energy balance and this lactational insulinoresistance can persist for subsequent pregnancies (Bossaert et al, 2008;De Koster and Opsomer, 2013;Zachut et al, 2013;Opsomer et al, 2017). Dairy cows insulinoresistant in late gestation produce lighter calves with reduced IGF1 plasma concentrations and increased insulinemia at birth (Kawashima et al, 2016). Effects on subsequent offspring production have not been studied but epidemiological data indicate a slightly reduced milk yield if offspring from dams inseminated at peak lactation (González-Recio et al, 2012).…”
Section: Effect Of Maternal Metabolismmentioning
confidence: 99%